Philanthropic foundations : new scholarship, new possibilities - Lagemann, Ellen Condliffe, 1945- (Philanthropic studies., 1999)
This book presents new scholarship about foundations such as Ford, Carnegie, Rockefeller, and Russell Sage, their history, and their impact on American society. -- Provided by publisher